The view from Hebrew: A commentary on Kidd and Garcia (2022). Issue 6 (December 2022) - Berman, Ruth A.
The commentary opens by pointing out why Kidd and Garcia's study is an important milestone in research on child language. The commentary goes on to survey insights from crosslinguistic research in the domain, focusing on the author's work in acquisition and development of Israeli Hebrew as a first language, from toddlers via schoolchildren to adolescents. And it calls for further research to enhance our understanding of what is universally shared by children across the world compared with developmental factors filtered by the impact of a particular target language.